Exploring Perceptions of Credible Science Among Policy Stakeholder Groups: Results of Focus Group Discussions About Nuclear Energy. (June 2016) - Berdahl, Loleen; Bourassa, Maureen; Bell, Scott; Fried, Jana
How do different stakeholder groups define credible science? Using original qualitative focus group data, this exploratory study suggests that while nuclear energy stakeholder groups consider the same factors when assessing credibility (specifically, knowledge source, research funding, research methods, publication, and replication), groups differ in their assessments of what constitutes expertise, what demonstrates (or reduces) trustworthiness, and the relative prioritization of expertise versus trustworthiness. Overall, these results suggest it is important for science communication to consider audience-specific credibility, and raise questions about the potential impact of both funding sources and predatory journals on the perceived credibility of scientists.